Study habits and attitudes of scholastic high achievers and low achievers in Quezon City high schools - Mendoza, Zenaida P. 1939- (Quezon City University of the Philippines, 1969)
The aims of the study are to obtain a descriptive profile of the study habits and attitudes of the Quezon City High School seniors, to determine relationships between study habits and some variables such as demographic and time, and to develop local norms on the Brown-Holtzman Survey of Study Habits and Attitudes for the use of all Quezon City High School seniors.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Study, Method of; Students -- Quezon City